أحاديث فضائل الصدقات والحج في كتاب فضائل الأعمال للكاندهلوي : دراسة حديثية نقدية - Fathul Bari Mat Jahya
This thesis covers an indepth study on Kitab Fada'il Al Acmal authored by Al Shaykh Al Kandahlawi, of which the content consist of many weak hadith, common stories and folk tales which are based upon accounts of qassasin or a story teller. In the effort to encourage virtuous deeds, the Kitab Fada'il Al Acmal has and are being widely read and taught in many places including mosques. The writer presented his evaluations on hadiths' mentioned in the topic the virtues of sadaqah or alms and the virtues of haji in which those hadith were not reported in the 6 reknown kitab of hadith. The writer has examined and analyzed the mentioned hadith prior to making critiques and exposition in determining their status. The writer begans with the biography on Shaykh Al Kandahlawi, his academic background, his position's amongst scholars. The introduction of Kitab Fada'il Al Acmal followed with the notion of practicing with a weak hadith in the Kitab Fada'il Al Acmal while stating other scholars 3 principles regarding practicing with a weak hadiths; firstly, permitting practices using a weak hadith; secondly, to unconditionally denounced the use of a weak hadith and thirdly keep objections on usage of a weak hadith moderately that conditionally carry some weight of other scholarly evidence that is stronger than it. Next is reviewing and study those hadith mentioned in the topics on the virtues of sadaqah and virtues of haji; 6 hadith sahih lidhatih (faultless) and 1 hadith sahih lighayrih (sound due to others) were found used in the 2 topics; as many as 14 hadith of hasan lidhatih (sources and reporters are known and clear) and 22 hadith of hasan lighayrih; 6 hadith of mursal (discontinuity in sanad) that are dacif (weak) and 19 hadith dacif (defect); 21 hadith of dacif jiddan (very weak) and 1 hadith as munkar (rejectable); 5 hadith of mawduc (fabricated); 2 hadith of unknown origin and another 2 hadith of untraceable sanad.